ماهية الرياضة في الأفلام السينمائية الرياضية العربية المصرية - لعياضي, عبد الحكيم; بن محمد, أحمد (جامعة الوادي - University of Eloued, 2022)
هذه الدراسة تهدف بالدرجة الأولى إلى معرفة ماهية الأفلام السينمائية العربية التي تطرقت للرياضة، منطلقة من إشكالية مفادها: هل نجحت أفلام السينما العربية الرياضية في توصيل ونقل مفهوم الرياضة الصحيح للمشاهد العربي؟، وباتباع المنهج الوصفي وأسلوب تحليل المضمون، فقد قامت بتحليل عينة واسعة من الأفلام السينمائية الرياضية المصرية التي بلغت 29 فيلما سينمائيا رياضيا بطريقة الحصر الشامل، وقد خلصت الدراسة إلى أن الأفلام السينمائية العربية الرياضية المصرية تركز على رياضة كرة القدم دون غيرها من الرياضات، وأنها لا تهتم بنقل المصطلحات الرياضية عموما، وبكونها تعمل على تدويل النمط الذكوري للرياضة فقط، وبأنها لا تشجع على الممارسة الرياضية وحديثها عن مواضيع أخرى غير الرياضة، وأخيرا بأنها لا تهتم بنقل المفهوم الصحيح للرياضة للمشاهد العربي. Abstract: This study aims primarily at knowing what are the Arab-Egyptian cinematic films that dealt with sports, starting from the problem of: Have Arab sports films succeeded in conveying and conveying the correct concept of sport to the Arab viewer? By following the descriptive approach and the method of content analysis, it analyzed a wide sample of The Egyptian sports films, which amounted to 29 sports films by a comprehensive inventory method, the study concluded that the Arab Egyptian sports films focus on football without other sports, and that they do not care about transferring sports terms in general, and that they work on internationalizing the male style of sports only And that it does not encourage sports practice and talk about topics other than sports, and finally that it does not care about conveying the correct concept of sports to the Arab viewer.
Sports Concepts in Arab-Egyptian Sports Movies
مقال
Keywords: رياضة ، أفلام سينمائية رياضية عربية مصرية